Esophageal Reconstruction - with Retroesternal Jejunum - Mayol, Ricardo; Mansho, Matsutoshi; Hatano, Rioji (Cirugía del Uruguay, 1980)
The conclusions about the study of jejunar vascularization are exposed. The different vascular patterns are planned in arder to perform this tec•nic.